Enterprise directory and security implementation guide designing and implementing directories in your organization - Carrington, Charles (Charles Dudley) (San Diego, Calif. : Academic Press, 2002)
The Internet is connecting enterprises into a global economy. Companies are exposing their directories, or a part of their directories, to customers, business partners, the Internet as a whole, and to potential "hackers." If the directory structure is compromised, then the whole enterprise can be at risk. Security of this information is of utmost importance. This book provides examples and implementation guidelines on building secure and structured enterprise directories. The authors have worked with corporations around the world to help them design and manage enterprise directories that operate efficiently and guard against outside intrusion. These experts provide the reader with "best practices" on directory architecture, implementation, and enterprise security strategies.
Foreword -- Acknowledgments -- Company Copyright Notices and Statements -- Chapter 1Introduction -- Chapter 2Directories, Security, and TigersOh, My! -- Chapter 3Directory Architecture -- Chapter 4More on LDAP -- Chapter 5Directories Within the Enterprise -- Chapter 6Implementation Considerations for the Enterprise Directory -- Chapter 7Enterprise Security -- Chapter 8The Security Strategy -- Chapter 9PKCS, PKIX, and LDAP -- Chapter 10Enterprise Security Scenarios -- Chapter 11Enterprise Security and Security Deployment Planning -- Glossary -- Index.
Includes index.
Keywords: Computer security equipment industry -- Directories; Electronic commerce -- Directories; Electronic books